A Comparison of Spectacles Purchased Online and in UK Optometry Practice. Issue 10 (October 2016) - Alderson, Alison J.; Green, Alison; Whitaker, David; Scally, Andrew J.; Elliott, David B.
ABSTRACT: Purpose: To compare spectacles bought online with spectacles from optometry practices. Methods: Thirty-three participants consisting of single vision spectacle wearers with either a low (N = 12, mean age 34 ± 14 years) or high prescription (N = 11, mean age 28 ± 9 years) and 10 presbyopic participants (mean age 59 ± 4 years) wearing progressive addition lenses (PALs) purchased 154 pairs of spectacles online and 154 from UK optometry practices. The spectacles were compared via participant-reported preference, acceptability, and safety; the assessment of lens, frame, and fit quality; and the accuracy of the lens prescriptions to international standard ISO 21987:2009. Results: Participants preferred the practice spectacles (median ranking 4th, IQR 1–6) more than online (6th, IQR 4–8; Mann-Whitney U = 7345, p < 0.001) and practice PALs (median ranking 2nd, IQR 1–4) were particularly preferred (online 6.5th, IQR 4–9, Mann-Whitney U = 455, p < 0.001). Of those deemed unacceptable and unsafe, significantly more were bought online (unacceptable: online 43/154 vs. practice 15/154, Fisher's exact p = 0.0001; unsafe: online 14/154 vs. practice 5/154, Fisher's exact p = 0.03). Conclusions: Participants preferred spectacles from optometry practice rather than those bought online, despite lens quality and prescription accuracy being similar. A greater number of online spectacles were deemed unsafe or unacceptable because of poor spectacle frame fit, poor cosmetic appearance, and inaccurate optical centration. This seems particularly pertinent to PAL lenses, which are known to increase falls risk. Recommendations are made to improve both forms of spectacle provision.